Studi Manajemen Konstruksi Bangunan Spillway dan Intake pada Bendungan Bulango Ulu Provinsi Gorontalo Menggunakan Metode Fasttrack dan Crashing - Dharyatiputri, Jihan Faradillah; Juwono, Pitojo Tri; Cahya, Evi Nur (Jurnal Talenta Sipil, 2024)
The construction of the Bulango Ulu Dam consists of several stages of work involving many resources, both human, material, and heavy equipment. Therefore, good construction management is needed so that project can be completed on time, cost efficiently, and good quality. This research was conducted with the aim of knowing which method is optimal in accelerating the Bulango Ulu Dam project. In this study, rescheduling is carried out with 2 project acceleration optimization methods, namely the fasttrack and crashing methods. The fasttrack method is done by changing the work dependency logic of the work on the critical path. While the crashing method is done by adding overtime for 2 hours per day to the work on the critical path as well. After optimizing the project, there were changes in term of cost and duration. In the fasttrack method, it has a cost efficiency of 0,26% and a duration effectiveness of 5,90%. While the crashing method has a cost efficiency of 1,27% and duration effectiveness of 4,46%. Based on the research conducted, the fasttrack method has a superior duration effectiveness than the crashing method which is 5,90%. While in terms of cost efficiency, the crashing method is superior to the fasttrack method by 1,27%.